Including Student Voices in Instructional Design: Community College Students with Below-Proficient Skills Talk About IL Instruction - Latham, Don; Gross, Melissa (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
First-year college students with below-proficient IL skill levels were identified through a standardized IL test. Interviews and focus groups were conducted with a subset of these students. This paper will focus on the findings of the focus groups and describe how these findings are informing the design of the intervention. Les étudiants universitaires de première année ayant une maîtrise de l'information inadéquate ont été identifiés au moyen d'un test normalisé sur la maîtrise de l'information. Des entrevues et des groupes de discussion se sont déroulés avec un sous-groupe de ces étudiants. Cette communication s'attarde aux résultats des groupes de discussion et décrit comment les résultats sont pris en compte dans la conception de l'intervention.